The Methodical Recommendations of Study of a Theme “Normal Forms for the Formulas of Algebra of the Statements” with use of Integrated Program Environment “MatLog” (Journal of Information Technologies in Education (ITE), 2008)
In the article the speech goes about implementation of new information technologies in process of mathematical logic learning at the Kherson State University. The questions of a technique of training to bases of mathematical logic with use of integrated program environment “MatLog” are considered.